ANALISIS PERTUMBUHAN PENDUDUK DAN SARANA SOSIAL DI KECAMATAN TANJUNG GADANG KABUPATEN SIJUNJUNG TAHUN 2010-2020 - Sari, ratna kurnia; Novio, Rery (JURNAL BUANA, 2024)
This research aims to (1) determine the population growth rate (2) determine the increase in social facilities (3) determine the adequacy of work facilities for population growth in the 2010-2020 time period. This type of research is classified as quantitative research, with secondary analysis, geometric methods with population growth rate formulas, research (1) shows that the highest population growth rate in 2010-2020 was Nagari Langki, Sibakur and Sinyamu with a percentage of 0.12%, and the lowest was Nagari Taraktak Baru and Timbulun with a percentage of 0.5%. So the rate of population growth in Tanjung Gadang District is relatively slow. (2) The highest increase in social facilities in Tanjung Gadang District in 2010-2020 was Nagari Tanjung Gadang with a total of 15 social facilities, and the lowest was Nagari Taratak Baru with a total of 4 facilities. (3) In 2010 the population was 22,866 people, then in 2020 it was 26,900 people, so that growth over a period of 10 years was 0.12%, calculated based on data, the educational facilities and health facilities are sufficient to serve all residents in 2020